Indigenous Knowledge and Local Power : Negotiating Change in West Africa - Easton, Peter (World Bank, Washington, DC, 2012)
Though the development, articulation, and systematization of indigenous knowledge in Africa are most often seen as issues of culture and local epistemology, they have at the same time critical power dimensions. The relation between local knowledge bases - and practitioners - on the one hand and central or Westernized ones on the other is manifestly a high-power/low-power situation, a matter most often quite acutely and accurately perceived by local people themselves. Until and unless the 'terms of trade" between these two spheres are significantly altered, or at least cast in a framework that promises some renegotiation, it is entirely understandable that the repositories of indigenous science would choose to keep it "off the market."